Co‐catalytic effect of Al‐Cr pillared montmorillonite as a new SCR catalytic support. Issue 11 (22nd February 2016) - Chen, Dingsheng; Cen, Chaoping; Feng, Jinxi; Yao, Chunyang; Li, Waiqing; Tian, Shuanghong; Xiong, Ya
Abstract: BACKGROUND: It is of great interest to use pillared clay (PILC) as a cheap support for a selective catalytic reduction (SCR) catalyst. Al‐Cr pillared clay (AlCr‐PILC) has high thermal stability due to the introduction of polycations of Al. As a support, AlCr‐PILC may show a co‐catalytic effect in SCR processes because chromium oxide itself is an active SCR catalyst. The aim of this work is to investigate the potential of AlCr‐PILC as a new low temperature SCR catalyst support. RESULTS: A series of AlCr‐PILC with Al:Cr molar ratio varying from 0:4 to 4:0 were successfully synthesized to support manganese and cerium active phase. MnCe/AlCr(2:2)‐PILC exhibited the highest NOx conversion close to 100% at 200–300 °C, and more than 90% N2 selectively over a wide temperature window of 140–300 °C. The catalytic activity of MnCe/AlCr‐PILC in terms of both NOx conversion and N2 selectivity is much higher than those of MnCe/Al‐PILC, MnCe/Cr‐PILC, AlCr‐PILC, and the simple mixed MnCeAlCr, indicating the co‐catalytic effect of AlCr‐PILC support. CONCLUSION: AlCr‐PILC is a very promising low‐temperature SCR catalyst support. The XRD, XPS, and H2 ‐TPR measurements prove that the co‐catalytic effect of AlCr‐PILC occurred via the strong interaction between MnCe and the AlCr‐PILC support. © 2016 Society of Chemical Industry